Factors influencing cross-border e-commerce enterprises’ engagement in vocational education partnerships - Zhan Guofang; Mohamad Sattar Rasul; Marlissa Omar (Intelektual Pustaka Media Utama, 2026)
This study investigates the factors influencing cross-border e-commerce enterprises’ willingness to engage in vocational education partnerships, addressing talent shortages and improving practical skills in vocational education. It contributes to the field by applying the theory of planned behavior (TPB) to the collaboration between this emerging industry and vocational education, offering a novel perspective on the framework’s utility. A quantitative research design was employed, with data collected through a survey of 401 cross-border e-commerce enterprises in Zhejiang Province, China. Key findings reveal that perceived benefits (PB) positively influence behavioral attitudes (BA), while perceived risks (PR) exert a negative effect. BA, subjective norms (peer influence (PI) and superior influence (SI)), and perceived behavioral control (self-efficacy and controllability) significantly predict cooperation intention (CI). These findings offer practical insights for policymakers and educational institutions. To promote effective collaboration, governments, and educational institutions should build trust through clear agreements and aligned expectations, while reducing PRs and enhancing PB. Additionally, providing training, consulting, and resource support can strengthen enterprises’ self-efficacy and controllability. Leveraging information sharing, promoting successful case studies, and utilizing the influence of peers and superiors will help mitigate uncertainties and enhance CI.